Find the challenging infinite sum

Calculus Level 5

In the diagram above, A B C ABC is a right triangle where A B = 1 \overline{AB}=1 and C A B = θ \angle CAB=θ . Point D D is on the hypotenuse such that A D : D C = t : 1 t \overline{AD}:\overline{DC}=t:1-t ( 0 < t < 1 ) (0<t<1) . Point E E is on B D BD such that B E C BEC is a right triangle whose hypotenuse is B C BC and whose area is S 1 S_1 . Repeat this process, starting with picking a point F F on the hypotenuse B C BC such that C F : F B = t : 1 t \overline{CF}:\overline{FB}=t:1-t ( 0 < t < 1 ) (0<t<1) . Let S n S_n be the area of the n n th right triangle.

The sequence of numbers a n a_n , for n 1 n≥1 , is such that the limit b n = lim θ 0 + S n θ a n \displaystyle b_n=\lim \limits_{θ \to 0+} \frac{S_n}{θ^{a_n}} exists and is nonzero. Denote X X as

X = n = 1 a n b n X= \displaystyle \sum_{n=1}^{\infty} a_nb_n where n = 1 b n = 1 2 \displaystyle \sum_{n=1}^{\infty} b_n=\frac12 .

Find 1 0 10 X \left \lfloor 10^{10} X \right \rfloor .

Notation: \lfloor \cdot \rfloor denotes the floor function .


The answer is 18458750876.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Mar 14, 2021

Consider one stage in this construction process, where one right-angled triangle has angle θ \theta and side x x , and the next right-angled triangle has angle ϕ \phi and corresponding side y y . Then sin ( θ + ϕ ) x = sin ϕ t x sec θ t sec θ sin ( θ + ϕ ) = sin ϕ t tan θ cos ϕ + t sin ϕ = sin ϕ tan ϕ = t 1 t tan θ \begin{aligned} \frac{\sin(\theta+\phi)}{x} & = \; \frac{\sin\phi}{t x \sec\theta} \\ t\sec\theta \sin(\theta + \phi) & = \; \sin\phi \\ t\tan\theta \cos\phi + t\sin\phi & = \; \sin\phi \\ \tan\phi & = \; \frac{t}{1-t}\tan\theta \end{aligned} Moreover, we note that y = x tan θ cos ϕ y \; = \; x \tan\theta \cos\phi

Thus, if θ n \theta_n (for n 0 n \ge 0 ) is the corresponding angle of the n n th right-angled triangle, then tan θ n + 1 = t 1 t tan θ n \tan\theta_{n+1} \; = \; \frac{t}{1-t} \tan\theta_n and hence tan θ n = ( t 1 t ) n tan θ n 0 \tan\theta_n \; = \; \left(\frac{t}{1-t}\right)^n \tan\theta \hspace{2cm} n \ge 0 Moreover, if x n x_n is the corresponding side of the n n th triangle, then x n + 1 = x n tan θ n cos θ n + 1 x_{n+1} \; = \; x_n \tan\theta_n \cos\theta_{n+1} and the area of the n n th triangle is S n = 1 2 x n 2 tan θ n S_n \; = \; \tfrac12x_n^2\tan\theta_n so that S n + 1 = 1 2 x n + 1 2 tan θ n + 1 = 1 2 x n 2 tan 2 θ n cos 2 θ n + 1 tan θ n + 1 = S n tan θ n tan θ n + 1 cos 2 θ n + 1 = S n ( t 1 t ) 2 n + 1 tan 2 θ cos 2 θ n + 1 \begin{aligned} S_{n+1} & = \; \tfrac12x_{n+1}^2 \tan\theta_{n+1} \; = \; \tfrac12x_n^2 \tan^2\theta_n \cos^2\theta_{n+1}\tan\theta_{n+1} \; = \; S_n \tan\theta_n \tan\theta_{n+1}\cos^2\theta_{n+1} \\ & = \; S_n \left(\frac{t}{1-t}\right)^{2n+1} \tan^2\theta \cos^2\theta_{n+1} \end{aligned} and so ( 1 t t ) ( n + 1 ) 2 S n + 1 = ( 1 t t ) n 2 S n tan 2 θ cos 2 θ n + 1 ( 1 t t ) ( n + 1 ) 2 S n + 1 tan 2 ( n + 1 ) θ = ( 1 t t ) n 2 S n tan 2 n θ cos 2 θ n + 1 \begin{aligned} \left(\frac{1-t}{t}\right)^{(n+1)^2}S_{n+1} &= \; \left(\frac{1-t}{t}\right)^{n^2}S_n \tan^2\theta \cos^2\theta_{n+1}\\ \left(\frac{1-t}{t}\right)^{(n+1)^2}\frac{S_{n+1}}{\tan^{2(n+1)}\theta} &= \; \left(\frac{1-t}{t}\right)^{n^2}\frac{S_n}{\tan^{2n}\theta} \cos^2\theta_{n+1} \end{aligned} so we deduce that S n = S 0 ( t 1 t ) n 2 tan 2 n θ j = 1 n cos 2 θ j = 1 2 ( t 1 t ) n 2 tan 2 n + 1 θ j = 1 n cos 2 θ j S_n \; = \; S_0 \left(\frac{t}{1-t}\right)^{n^2} \tan^{2n}\theta \prod_{j=1}^n \cos^2\theta_j \; = \; \frac12 \left(\frac{t}{1-t}\right)^{n^2} \tan^{2n+1}\theta \prod_{j=1}^n \cos^2\theta_j Thus it follows that lim θ 0 + S n θ 2 n + 1 = 1 2 ( t 1 t ) n 2 \lim_{\theta \to 0+} \frac{S_n}{\theta^{2n+1}} \; =\; \frac12\left(\frac{t}{1-t}\right)^{n^2} so we deduce that a n = 2 n + 1 b n = 1 2 ( t 1 t ) n 2 n 0 a_n \; = \; 2n+1 \hspace{1cm} b_n \; = \; \frac12\left(\frac{t}{1-t}\right)^{n^2} \hspace{2cm} n \ge 0 Since b 0 = 1 2 b_0 = \tfrac12 and we require the sum of the b n b_n to be less than 1 2 \tfrac12 , we must be ignoring the original triangle A B C ABC in these calculations, and we need to find 0 < t < 1 0 < t <1 such that 1 = 2 n = 1 b n = n = 1 q n 2 = 1 2 ( ϑ 3 ( 0 , q ) 1 ) 1 \; = \; 2\sum_{n=1}^\infty b_n \; = \; \sum_{n=1}^\infty q^{n^2} \; =\; \frac12\left( \vartheta_3(0,q) - 1\right) where q = t 1 t q = \tfrac{t}{1-t} . Solving this equation numerically gives q = 0.705346681379806989636379706394... t = 0.413608968241640136350617724053 q \; = \; 0.705346681379806989636379706394... \hspace{2cm} t \; = \; 0.413608968241640136350617724053 and hence X = n = 1 a n b n = 1 2 n = 1 ( 2 n + 1 ) q n 2 = 1.84587508767744720084799289178 X \; =\; \sum_{n=1}^{\infty}a_nb_n \; = \; \frac12\sum_{n=1}^{\infty}(2n+1)q^{n^2} \; = \; 1.84587508767744720084799289178 and hence 1 0 10 X = 18458750876 \lfloor 10^{10}X \rfloor \; = \; \boxed{18458750876} Although I am not immediately aware of a closed form for X X , it is easy to find X X to the required degree of accuracy. Since q < 3 4 q < \tfrac34 , we can show that ( 2 n + 1 ) q n 7 q 3 < 3 n N (2n+1)q^n \le 7q^3 < 3 \hspace{2cm} n \in \mathbb{N} and hence n = N + 1 ( 2 n + 1 ) q n 2 3 n = N + 1 q n ( n 1 ) 3 q N n = N + 1 q ( n 1 ) 2 3 q N n = N 2 q n = 12 ( 3 4 ) N ( N + 1 ) \sum_{n=N+1}^\infty (2n+1)q^{n^2} \; \le \; 3\sum_{n=N+1}^\infty q^{n(n-1)} \; \le \; 3q^N \sum_{n=N+1}^\infty q^{(n-1)^2} \; \le \; 3q^N \sum_{n=N^2}^\infty q^n \; = \; 12\big(\tfrac34\big)^{N(N+1)} Thus n = N + 1 ( 2 n + 1 ) q n 2 < 5 × 1 0 11 \sum_{n=N+1}^\infty (2n+1)q^{n^2} \; < \; 5 \times 10^{-11} provided that 12 ( 3 4 ) N ( N + 1 ) < 5 × 1 0 11 12\big(\tfrac34\big)^{N(N+1)} < 5\times10^{-11} or N ( N + 1 ) > 11 + log 10 2.4 log 10 4 3 = 91.09 N(N+1) > \frac{11+\log_{10}2.4}{\log_{10}\frac43} = 91.09 , and hence provided that N 10 N \ge 10 . Thus we can get 10 10 decimal place accuracy for X X by calculating n = 1 10 ( 2 n + 1 ) q n 2 \sum_{n=1}^{10}(2n+1)q^{n^2}

Too long......................

. . - 2 months, 4 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...